2007
DOI: 10.1111/j.1600-0420.2007.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation syndrome: prevalence and inheritance in a subisolate of the Finnish population

Abstract: In this population-based family study, ES is consistent with an autosomal dominant trait with incomplete penetrance, where the penetrance is more reduced in males than in females. However, the presence of ES was a greater risk factor for developing glaucoma in males than in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…The involvement of genetic factors in the pathogenesis of PEX was initially supported by evidence of strong familial aggregation [19,20]. However, a simple inheritance model has not been identified, which suggests a complex inheritance pattern resulting from interplay of multiple genetic and environmental factors [21].…”
Section: Pathogenesismentioning
confidence: 97%
“…The involvement of genetic factors in the pathogenesis of PEX was initially supported by evidence of strong familial aggregation [19,20]. However, a simple inheritance model has not been identified, which suggests a complex inheritance pattern resulting from interplay of multiple genetic and environmental factors [21].…”
Section: Pathogenesismentioning
confidence: 97%
“…The heritability of IOP was 0.48, which is higher than that in other studies. 11,12,48 The higher heritability is most likely due, at least in part, to the lesser variation in other environments and more genetic heterogeneity underlying IOP levels.…”
Section: Discussionmentioning
confidence: 97%
“…Another possible reason for the variation is that the minimum age of the study population varied from 40 to 60 years. [10][11][12][13][14][15][16][19][20][21][22][23][24]27,28 As age is a constant risk factor for PEX, this can explain some of the differences reported. Despite these differences, there do appear to be racial, genetic, or geographic factors that impact prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The prevalence of PEX has been reported from different populations [9][10][11][12][13][14][15][16][17][18][19][20] and is known to be high in Scandinavian countries and Greece. [21][22][23][24][25][26] Cross-sectional population-based studies have reported the prevalence of PEX in the Indian population and it varied from 2% to 6% in subjects aged 40 years and older. [27][28][29][30] Older age was found to be a significant risk factor.…”
mentioning
confidence: 99%